2013
DOI: 10.1111/cod.12139
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin loss‐of‐function mutations and atopic dermatitis as risk factors for hand eczema in apprentice nurses: part II of a prospective cohort study

Abstract: SummaryBackground/objectivesEnvironmental exposure and personal susceptibility both contribute to the development of hand eczema. In this study, we investigated the effect of loss-of-function mutations in the filaggrin gene (FLG), atopic dermatitis and wet work exposure on the development of hand eczema in apprentice nurses.MethodsDutch apprentice nurses were genotyped for the four most common FLG mutations; atopic dermatitis and hand eczema history were assessed by questionnaire. Exposure and hand eczema duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 56 publications
1
75
0
1
Order By: Relevance
“…These results are similar to those of Visser et al, 27 who suggested that the influence of FLG mutations on hand dermatitis in Dutch apprentice nurses differed between individuals with and without AD. Visser et al 27 showed that the highest risk of hand dermatitis during traineeships was found among participants with concomitant FLG mutations and AD (OR 3.6).…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those of Visser et al, 27 who suggested that the influence of FLG mutations on hand dermatitis in Dutch apprentice nurses differed between individuals with and without AD. Visser et al 27 showed that the highest risk of hand dermatitis during traineeships was found among participants with concomitant FLG mutations and AD (OR 3.6).…”
Section: Discussionsupporting
confidence: 91%
“…18 Increased prevalences of polysensitization and contact sensitization to fragrances (ie, balsam of Peru) 12,19 and metals were also shown in patients with AD. 20 22,23 and lower prevalence of ACD in patients with severe AD. 24 A few studies also suggest decreased responses to strong and clinically irrelevant sensitizers, such as dinitrochlorobenzene (DNCB); in vitro studies with PBMCs show impaired cytokine production after stimulation with contact allergens (ie, nickel).…”
mentioning
confidence: 93%
“…24 A few studies also suggest decreased responses to strong and clinically irrelevant sensitizers, such as dinitrochlorobenzene (DNCB); in vitro studies with PBMCs show impaired cytokine production after stimulation with contact allergens (ie, nickel). 22,25 Newell et al 26 recently reported attenuated responses to DNCB and T H 2 skewing (with decreased IFN-g and increased IL-4 levels) in normalappearing skin from atopic compared with healthy subjects. The T H 2-polarized responses were independent of filaggrin (FLG) mutation status, 27 which is consistent with the lack of association between ACD and FLG mutations in most studies.…”
mentioning
confidence: 98%
“…Genetics, other than the predisposition relating to atopic dermatitis, have also been suggested to play a role in the development of HE (10). One study investigated a loss-of-function mutation in the filaggrin gene, and found that the combination of filaggrin gene mutation and atopic dermatitis is a greater risk factor for HE than atopic dermatitis alone (11).…”
mentioning
confidence: 99%